2005
DOI: 10.1515/cclm.2005.185
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the technical performance of novel holotranscobalamin (holoTC) assays in a multicenter European demonstration project

Abstract: A commercially available holotranscobalamin (holo-TC) radioimmunoassay (RIA) (Axis-Shield, Dundee, Scotland) was evaluated in four laboratories and compared with a holoTC ELISA run in one laboratory. The performance of the holoTC RIA assay was comparable in three of the four participating laboratories. The results from these three laboratories, involving at least 20 initial runs of "low", "medium" and "high" serum-based controls (mean holoTC concentrations 34, 60 and 110 pmol/L, respectively) yielded an intra-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 34 publications
(26 reference statements)
2
34
0
Order By: Relevance
“…The 40 pmol/L cut-off value we selected was also reported by other authors (18)(19)(20). We also verified the predictive ability of HoloTC at this threshold for selected tB 12 cut-off points.…”
Section: Discussionsupporting
confidence: 80%
“…The 40 pmol/L cut-off value we selected was also reported by other authors (18)(19)(20). We also verified the predictive ability of HoloTC at this threshold for selected tB 12 cut-off points.…”
Section: Discussionsupporting
confidence: 80%
“…The test is thought to have sensitivities and specificities comparable to that of serum vitamin B12 when compared to MMA elevations (48). Several studies suggested that holo-TC-II slightly outperformed the serum vitamin B12 test (65,66). The specificity of the holo-TC-II test remains unclear.…”
Section: Holo-tc-ii Testmentioning
confidence: 99%
“…Laboratories use cut-offs that range between 11 and 41 pmol/L (66). Relationships between chosen cut-offs and resultant outcomes warrant additional research.…”
Section: Holo-tc-ii Testmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the Axis-Shield active B12 EIA kit (9) and diluted samples 1:1 in sample diluents according to the kit insert. In addition, we used our in-house ELISA (7,10) . The two samples obtained as part of the CobaSorb test are always run on the same day and, because of that, our main interest was to explore the intra-assay variation of the EIA kit.…”
mentioning
confidence: 99%